Framework for an Evidence-Based Physical Activity Intervention: Promoting Healthy Communities - Bruno, Laura E. (Building Healthy Academic Communities Journal, 2017)
Purpose: Identifying best practices in successful community based intervention programs is critical to improving the health concerns that currently afflict our nation. The purpose of this study was to determine the effectiveness of a community-based physical activity (PA) intervention program in order to share an evidence-based framework that can be used in community settings, including academic communities. The specific objectives of this study were to determine the effectiveness of a community based PA intervention program, specifically noting changes in perceived levels of (a) self-esteem, (b) body size satisfaction, (c) frequency of physical activity and (d) commitment levels the longer a participant engaged in the program. Method: The cross-sectional, quantitative self-report survey design utilized a 29-item web-based questionnaire. A sample of participants (N = 383 (Mage = 43 years; SD = 7 years; 100% women) from the Mullica Hill Women’s Triathlon Club self-selected to participate. Results: Independent sample t-tests ascertained that the longer a participant engaged in the program, the more her perceived self-esteem improved and the more committed she became to PA. Chi square goodness of fit analyses further demonstrated that a woman’s age impacted her level of satisfaction with her body. Conclusions: Opportunities to participate in a community based intervention program should be extended throughout all communities in an effort to improve holistic well-being. Further, type and duration as well as point of data collection of such programs should be differentiated in future research.